(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Production of Biofuel in higher yield by processing lignocellulosic biomass has been limited by the characteristics of conventional saccharomyces cerevisae which can utilize lesser number of carbon sources and has very less thermotolerance. Further, complex structure of cellulose and hemicellulose bounded by fibrils of lignin makes it difficult to efficiently pre-treat these feedstocks by acidic and enzymatic hydrolysis. In current review, we discuss the plethora of methodologies which are a boon in production of biofuels from various lignocellulosic raw materials due to advancement in forte of Genome editing technologies, Plant Biotechnology, metabolic engineering and nanobiotechnology. Utilizing metabolically engineering strategies using non conventional microbial species, developing synthetic gene constructs, knocking out genes like COMT, mutating CESA genes using CRISPR Cas9 and RNA interference approaches has been shown to decrease the crystalline structure of Cellulose and enhance the availability of cellulose per unit area, expose lignin to efficient pre-treatment and accelerate conversion rate. Transferring gene encoding alpha amylase and glucoamylase(SWA2 and GAM1) from conventional yeast strains to uncommon strains like H.polymorpha has improvised the efficiency of glucose and xylose utilisation for industrial production of Biofuel. Application of metal oxides of nanomaterials and specifically gold nanoparticles have enhanced the yield of biofuels. Magnetic nanoparticles have been used to embed the enzymes involved in pre-treatment of Lignocellulosic material resulting in better encapsulation and sustainable use of these enzymes over multiple cycles.